Comparison of L-lysine aescinat and Kontrikal blood flow and morphology of the vessel in the brain is awake rabbits general vibration - A. G. Belyakova (Zaporožskij Medicinskij Žurnal)
Chronic experiments on conscious rabbits with needle-shaped platinum electrodes implanted into the brain cortex, thalamus and hypothalamus were made. The modeling of wide-frequency vibration causes slowing down of cerebral blood flow. L-lysine aescinat prevents changing of blood flow in hypothalamus, causes growth into the brain cortex and not significant lowering in thalamus. Contrykal provides absolute growth of a blood circulation in all structures that were studied. In acute experiments on conscious rabbits wide-frequency vibration causes spasm arterioles and dilation of veins. According to histologic dates L-lysine aescinat prevents changes in the bloodstream better than Contrykal.